In defense of the domestic market. Japanese imports and textile entrepreneurs in Peru, 1929-1939 - Lobo Collantes, Juan Franco (2019)
This article analyzes the impact of the financial crisis of 1929 and large Japanese textile imports on the Peruvian cotton textile sector in the 1930s, and how leading enterprises defended themselves. We start by describing the characteristics of the enterprises that led the textile industry before 1929. We then suggest that the 1929 crisis and the increase in Japanese imports led textile entrepreneurs to mobilize their capacity to influence the government in order to protect their companies, something that had not occurred in previous periods.